Optimal delegation of sequential decisions: The role of communication and reputation - Alp Atakan; Levent Koçkesen; Elif Kubilay (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
We analyze delegation of a set of decisions over time by an informed principal to a potentially biased agent. Each period the principal observes a state of the world and sends a 'cheap-talk' message to the agent, who is privately informed about her bias. We focus on principal-optimal equilibria that satisfy a Markovian property and show that if the potential bias is large, then the principal assigns less important decisions in the beginning and increases the importance of decisions towards the end. In the beginning of their relationship, the biased agent acts exactly in accordance with the principal's preferences, while towards the end, she starts playing her own favorite action with positive probability and gradually builds up her reputation. Principal provides full information in every period as long as he has always observed his favorite actions in the past. If we interpret the evolution of the importance of decisions over time as the career path of an agent, this finding fits the casual observation that an agent's career usually progresses by making more and more important decisions and provides a novel explanation for why this is optimal. We also show that the bigger the potential conflict of interest, the lower the initial rank and the faster the promotion.
Keywords: D82; D83; D23; 330; Delegation; Communication; Cheap Talk; Reputation; Career Path; Gradualism; Starting Small